2020
DOI: 10.1016/j.autneu.2019.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus (HPV) vaccine and autonomic disorders: a position statement from the American Autonomic Society

Abstract: Introduction: Human papillomavirus (HPV) vaccination has been anecdotally connected to development of dysautonomia, chronic fatigue, complex regional pain syndrome and postural tachycardia syndrome. Objectives: To critically evaluate a potential connection between HPV vaccination and above noted conditions. Methods: We reviewed the literature containing the biology of the virus, pathophysiology of infection, epidemiology of associated cancers, indications of HPV vaccination, safety surveillance data and publis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…Other musculoskeletal conditions, such as rheumatoid arthritis, may also increase the risk [20]. Although CRPS and other autonomic disorders have been anecdotally reported as adverse events after human papillomavirus (HPV) vaccination, review of published reports and a small population-based case series found no statistically significant correlation [21][22][23].…”
Section: Risk Factorsmentioning
confidence: 99%
“…Other musculoskeletal conditions, such as rheumatoid arthritis, may also increase the risk [20]. Although CRPS and other autonomic disorders have been anecdotally reported as adverse events after human papillomavirus (HPV) vaccination, review of published reports and a small population-based case series found no statistically significant correlation [21][22][23].…”
Section: Risk Factorsmentioning
confidence: 99%
“…More recently, autoantibodies against G-protein-coupled receptor subtypes have been reported to be elevated in POTS [ 17 , 18 , 19 , 20 , 21 ]. There are also a number of reports of POTS developing subsequent to human papilloma virus immunization [ 22 , 23 , 24 ], implicating a potential role of inflammation and/or molecular mimicking as etiologies for the development of POTS. There is evidence that predisposing viral infections, celiac disease, and thyroiditis, all of which have a significant immune response, may be associated with POTS [ 6 , 10 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Park et al reported on a 5-month-old child who developed paroxysmal supraventricular tachycardia within four to six hours after each of the two, four, and six-month diphtheria, tetanus, and pertussis (DTaP) vaccinations [ 3 ]. While there have been many case reports with a multitude of similar symptoms suggesting an association between the human papillomavirus vaccination causing postural orthostatic tachycardia syndrome (POTS) and dysautonomia (with some suggesting an immune-mediated autonomic dysfunction [ 4 - 5 ]), the American Autonomic Society published a position paper refuting any such link [ 6 ]. Hviid et al found the temporal association possible but unlikely [ 7 ].…”
Section: Discussionmentioning
confidence: 99%